Dignity and psychosocial related variables in elderly advanced cancer patients - Carla M. Martín-Abreu; Raquel Hernández; Patricia Cruz-Castellanos; Ana Fernández-Montes; David Lorente-Estellés; Helena López-Ceballos; Lorena Ostios-Garcia; Mónica Antoñanzas; Paula Jiménez-Fonseca; Teresa García-García; Caterina Calderon (BMC Geriatrics, 2022)
Abstract Introduction Most cancers occur in older individuals, who are more vulnerable due to functional impairment, multiple comorbidities, cognitive impairment, and lack of socio-familial support. These can undermine patients’ sense of dignity. This study seeks to compare dignity scores in older patients with advanced cancer on sociodemographic and clinical variables and analyze the predictive value of anxiety, depression, functional limitations, and social support on dignity scores. Methods A prospective, multicenter, observational study conducted with participation of 15 hospitals in Spain from February 2020 to October 2021. Patients with newly-diagnosed, advanced cancer completed the dignity (PPDS), anxiety and depression (BSI), Social Support (Duke–UNC-11), and functional limitations (EORTC-C30) scales. Lineal regression analyses explored the effects of anxiety, depression, functional status, and social support on dignity, adjusting for sociodemographic and clinical variables. Results A total of 180 subjects participated in this study. The results of the correlation analysis revealed that dignity correlated negatively with anxiety, depression, and sex, and positively with social support, functional status, and longer estimated survival. Thus, women, and more anxious and depressed individuals scored lower on the dignity scale, whereas patients with more social support, fewer functional limitations, and longer estimated survival scored higher. Conclusion In conclusion, being female, having a lower educational level, lower estimated survival, depression, anxiety, less social support, and limited functionality are correlated with less dignity in the elderly with advanced cancer. It is a priority to manage both physical and psychological symptoms in patients with unresectable advanced cancer to mitigate psychological distress and increase their sense of dignity.